Future Prospect of Oral Microbiota Influencing Allergy/Asthma Development - Cai, Yue; Zhao, Yanqin; Kang, Yongbo; Yang, Ying (Frontiers in Microbiology, 2022)
Allergic diseases have become a primary public health issue in a moderately prosperous society. Colonization of microorganisms early in life appears to be significant in guiding the regulation of childhood immune system maturation and allergy development. Since the oral cavity is the first position where most foreign antigens meet the immune system, the oral microbiota may play a key role in the development of allergies. However, the study on the effects of oral microorganisms on allergy/asthma is very restricted and should be actively investigated. It requires considerable effort to enrich our knowledge in this area of the relationship between the oral cavity and allergy/asthma. To promote the rapid progress of relevant research. In this review, we aimed to provide several insights into the role of the oral microbiota in allergy/asthma while prospecting future directions.